Evaluación técnico-financiera del diseño de un Gun Barrel a partir de un tanque de almacenamiento existente para el mejoramiento del proceso de separación de fluidos en la estación C de un campo en la cuenca Caguán-Putumayo (2018)
The development of this project has as object the technical and financial evaluation of a Gun Barrel Tank’s design to improve the fluid separation process (emulsion treatment) in Station C located in a Field in Caguán-Putumayo Basin. The selection of the required equipment for the treatment of fluids was done based on the results of a previous simulation which was developed therefore to optimize the process and reduce energy consumption in the treatment plant; which showed an outlet stream from the separator with a BSW% and gas content higher than the current one, thus, this equipment is required for its management. Starting the development of the project, the description of the generalities of the field in which Station C is located is made, history and localization are included; continuing, equipment and operational parameters in charge of the treatment of the fluids coming form the well are described, alongside its characterization.